2021
DOI: 10.3390/cancers13020286
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Response to Immune Checkpoint Inhibitors in Association with Genomic and Clinical Features in Patients with Head and Neck Squamous Cell Carcinoma (HNSCC)

Abstract: Background: We sought to compare patterns of response to immune checkpoint inhibitors (ICI) with respect to clinical and genomic features in a retrospective cohort of patients with recurrent/metastatic (R/M) head and neck squamous cell carcinoma (HNSCC). Methods: One hundred seventeen patients with R/M HNSCC treated with ICI were included in this study. Tumor growth kinetics (TGK) prior to and TGK upon immunotherapy (IO) was available for 49 patients. The TGK ratio (TGKR, the ratio of tumor growth velocity bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…By multivariate analysis, it was found that MDM2/MDM4 amplification and EGFR mutations were associated with TTF < 2 months. The presence of MDM2 amplification and EGFR mutations in patients with HPD were also found in a clinical study by Singavi et al [50] and Economopoulou et al [51] . The MDM2 protein encoded by the MDM2 gene is a major negative regulator of the p53 protein.…”
Section: Mdm2/mdm4 Amplification and Egfr Mutationsupporting
confidence: 62%
See 1 more Smart Citation
“…By multivariate analysis, it was found that MDM2/MDM4 amplification and EGFR mutations were associated with TTF < 2 months. The presence of MDM2 amplification and EGFR mutations in patients with HPD were also found in a clinical study by Singavi et al [50] and Economopoulou et al [51] . The MDM2 protein encoded by the MDM2 gene is a major negative regulator of the p53 protein.…”
Section: Mdm2/mdm4 Amplification and Egfr Mutationsupporting
confidence: 62%
“…[ 50 ] and Economopoulou et al . [ 51 ] . The MDM2 protein encoded by the MDM2 gene is a major negative regulator of the p53 protein.…”
Section: Molecular Mechanism Underlying Hpdmentioning
confidence: 99%
“…Ferrara et al ., [23] have defined HPD as progressive disease by response evaluation criteria in solid tumors criteria at first evaluation and a difference in tumor growth ratio (TGR) higher than 50% (calculated comparing pre- and postimmunotherapy TGR). Similarly, Economopoulou et al ., [24] have defined radiologic HPD as the presence of tumor growth kinetics ratio (TGK) (ratio between TGK upon treatment and TGK before treatment) >2. However, the authors observed that several patients experienced clinical HPD without meeting radiologic criteria, suggesting that HNSCC could own intrinsic features that complicate the assessment of response based only on radiologic criteria and raising the question of the incorporation of clinical benefit endpoints into the definition of response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…22 Although HPD was found in 2016, its definition and diagnostic criteria have not been unified. It is worth noting that continuous studies have shown that HPD is associated with poor OS, 11,13,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and may even accelerate death in bladder carcinoma and squamous cell carcinoma. 15,31 Moreover, a shorter period of PFS has a certain contribution to the prognosis and even death.…”
Section: Definition Of Hpdmentioning
confidence: 99%
“…55 Some studies have also shown that patients with HPD were younger than patients with non-HPD in non-small cell lung cancer (NSCLC) and in neck squamous cell carcinoma (HNSCC). 31,34,37,56 In summary, to determine the significance of age as a clinical characteristic for HPD will require prospective studies with large samples.…”
Section: Clinical and Molecular Characteristics Of Hpdmentioning
confidence: 99%